Moving beyond correlations in assessing the consequences of poverty. [article]. - Duncan, Greg J.
In the United States, does growing up in a poor household cause negative developmental outcomes for children? Hundreds of studies have documented statistical associations between family income in childhood and a host of outcomes in childhood, adolescence, and adulthood. Many of these studies have used correlational evidence to draw policy conclusions regarding the benefits of added family income for children, in particular children in families with incomes below the poverty line. Are these conclusions warranted? After a review of possible mechanisms linking poverty to negative childhood outcomes, we summarize the evidence for income's effects on children, paying particular attention to the strength of the evidence and the timing of economic deprivation. We demonstrate that, in contrast to the nearly universal associations between poverty and children's outcomes in the correlational literature, impacts estimated from social experiments and quasi-experiments are more selective. In particular, these stronger studies have linked increases in family income to increased school achievement in middle childhood and to greater educational attainment in adolescence and early adulthood. There is no experimental or quasi-experimental evidence in the United States that links child outcomes to economic deprivation in the first several years of life. Understanding the nature of socioeconomic influences, as well as their potential use in evidence-based policy recommendations, requires greater attention to identifying causal effects. -- (from the author)